Why does family doctor should learn geriatric - Życzkowska, Jolanta (Przewodnik Lekarza/Guide for GPs, 2006)
The rapid population ageing resulting from the increasing average length of life and the decrease of birth rate is reflected in the percentage of older patients visiting their general practitioners. A family doctor has to take into consideration that more and more patients will be at a very advanced age and that is why he will have to cope with many complicated and complex problems resulting from polypathology and a varied course of illness. He also must be aware that more often than among younger patients he can find diagnostic and therapeutic difficulties. Lack of characteristic symptoms, presence of non-characteristic or non-specific symptoms, difficult co-operation with patients, frequent bad economic situation and lack of help from family or friends, make it really difficult to cope with health problems of elderly people.